Alterations of metabolic enzymes in Australian bass, Macquaria novemaculeata, following exposure to petroleum hydrocarbons - Nugegoda, D.; Cohen, A.; Gagnon, Marthe Monique (SETAC, 2008)
Australian bass Macquaria novemaculeata were exposed to the water-accommodated fraction of Bass Strait crude oil, dispersed crude oil, or burnt crude oil to assess sublethal effects of oil spill remediation techniques on fish. Fish were exposed to these treatments for 16 days either through the water column or by way of a pre-exposed diet of amphipod Allorchestes compressa. Fish gills, liver, and white muscle were sampled and cytochrome C oxidase (CCO) and lactate dehydrogenase (LDH) activities quantified. In all treatments containing fish exposed by way of the water column, aerobic activity increased in the gills, whereas a decrease of this enzymic activity was observed in the liver and white muscle. Exposures by way of the food pathway indicated similar trends. Anaerobic (LDH) activity increased in the gills, liver, and white muscle after waterborne exposures. Stimulation in anaerobic activity also occurred in the liver and white muscle of fish after exposure to contaminated food. CCO activity in the gills was the most sensitive biomarker when monitoring waterborne exposures to petroleum hydrocarbons. In the gills, the dispersed oil treatment resulted in the most pronounced biological response, suggesting that in the short term the use of dispersants on an oil slick might cause the most perturbations to fish metabolism.